Efektivitas Model Pembelajaran Problem Based Learning (PBL) dalam Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik Kelas VII-B SMP Negeri 6 Mataram - Hidayati, Nurul; Azmi, Syahrul; Sadri, Samaratus (FKIP Universitas Mataram, 2025)
Abstract This research aims to investigate the effectiveness of the Problem-Based Learning (PBL) model in enhancing the learning activities and outcomes of seventh-grade students in SMPN 6 Mataram, particularly for students with diverse mathematical abilities. Employing a collaborative Classroom Action Research (CAR) approach, the study was conducted in three cycles consisting of planning, implementation, observation, and reflection. Data collection methods included observation of learning activities and achievement tests. The research findings revealed a significant increase in student learning engagement, from 59.37% in cycle I to 81.25% in cycle III, as well as an improvement in learning mastery from 59.52% in cycle I to 85.71% in cycle III. These findings indicate that the Problem-Based Learning (PBL) model successfully encouraged active student involvement in learning activities and enhanced their understanding of the subject matter. This research recommends the adaptive and creative implementation of the Problem-Based Learning (PBL) model, as well as the development of varied learning activities to cater to the needs of students.